2009
DOI: 10.4049/jimmunol.0901412
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Are Required for the Production of Blister-Inducing Autoantibodies in Experimental Epidermolysis Bullosa Acquisita

Abstract: Epidermolysis bullosa acquisita is a prototypical organ-specific autoimmune disease caused by autoantibodies against type VII collagen of the dermal-epidermal junction. Although mechanisms of autoantibody-induced blister formation were extensively characterized, the initiation of autoantibody production in autoimmune blistering diseases is still poorly defined. In the current study, we addressed the role of T cells for the production of blister-inducing autoantibodies in mice immunized with type VII collagen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
2
45
0
1
Order By: Relevance
“…ABD have been classically defined as B cellmediated diseases due to the presence of both 1) spontaneously appearing, intraepidermal clinical blisters after injection of human sera into neonatal mice, and 2) epidermal-specific autoantibodies whose serum titers classically correlate with clinical activity and disease severity as demonstrated by IIF and ELISA [1][2][3][4]20]. Our in situ results document the involvement of other immune cells in ABD lesional skin, indicating that other immune system components may be important in these diseases [21][22][23][24][25][26][27]. In our study, we did not attempt to demonstrate a precise pathogenic role of these molecules; however, further investigation is warranted in this area.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…ABD have been classically defined as B cellmediated diseases due to the presence of both 1) spontaneously appearing, intraepidermal clinical blisters after injection of human sera into neonatal mice, and 2) epidermal-specific autoantibodies whose serum titers classically correlate with clinical activity and disease severity as demonstrated by IIF and ELISA [1][2][3][4]20]. Our in situ results document the involvement of other immune cells in ABD lesional skin, indicating that other immune system components may be important in these diseases [21][22][23][24][25][26][27]. In our study, we did not attempt to demonstrate a precise pathogenic role of these molecules; however, further investigation is warranted in this area.…”
Section: Discussionmentioning
confidence: 73%
“…Previous authors have found some alteration in the T cell immune response, and/or alterations in T cell numbers detected by several methods including FACS analysis in ABD [21][22][23][24][25][26][27][28]. One group of authors have shown that T cells are required for the production of blister inducing autoantibodies in experimental epidermolysis bullosa acquisita [24]. Another study with untreated BP patients compared to controls has shown low CD4+, CD25 bright+, FOXP3+ cells were significantly reduced in BP [25].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, so far, detailed investigations on the cellular requirements in the early pathogenesis of these animal models had not been performed. The MHC association of immunization-induced AIBD (19,22) pointed toward a contribution of T cells, which was confirmed by a resistance of T cell-deficient mice to develop epidermolysis bullosa acquisita (EBA) (23). It has so far remained unclear which T cell subsets and which APCs contribute to the loss of tolerance to structural proteins of the skin in AIBD.…”
mentioning
confidence: 94%
“…4 In addition, a key role of T cells in the initiation of autoimmunity against type VII collagen has been demonstrated recently. 5 Experimental EBA, which reproduces both the autoimmune response and immunopathologic, histologic, and clinical findings in patients with EBA, can be induced in susceptible mice by immunization with recombinant murine type VII collagen. 6 Therefore, EBA emerges as a model disease to study fundamental biologically and clinically crucial aspects of antibody-mediated, organ-specific autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%